Role of factor H-related protein 3 in Pseudomonas aeruginosa bloodstream infections - González-Alsina, Alex; Martín-Merinero, Héctor; Mateu-Borrás, Margalida; Verd, María; Doménech-Sánchez, Antonio; Goldberg, Joanna B.; Rodríguez de Córdoba, Santiago; Albertí, Sebastián (Frontiers in Immunology, 2024)
Pseudomonas aeruginosa is a leading cause of nosocomial bloodstream infections. The outcome of these infections depends on the virulence of the microorganism as well as host-related conditions and factors. The complement system plays a crucial role in defense against bloodstream infections. P. aeruginosa counteracts complement attack by recruiting Factor H (FH) that inhibits complement amplification on the bacterial surface. Factor H-related proteins (FHRs) are a group of plasma proteins evolutionarily related to FH that have been postulated to interfere this bacterial evasion mechanism.In this study, we demonstrate that FHR-3 competes with purified FH for binding to P. aeruginosa and identify EF-Tu as a common bacterial target for both complement regulator factors. Importantly, elevated levels of FHR-3 in human serum promote complement activation, leading to increased opsonization and killing of P. aeruginosa. Conversely, physiological concentrations of FHR-3 have no significant effect. Our findings suggest that FHR-3 may serve as a protective host factor against P. aeruginosa infections.